Kunci Sukses Pembelajaran Efektif: Tinjauan Sistematic Literature Review Memahami Hubungan Gaya Kognitif, Regulasi Diri, dan Motivasi - Pratama, Indra Gunawan (Psycho Aksara : Jurnal Psikologi, 2024)
Effective education requires a profound understanding of the psychological factors influencing the learning process. In this context, this research conducts a systematic review of existing literature to explore the relationship between cognitive styles, self-regulation, and motivation in achieving effective learning. Cognitive styles encompass individual preferences in processing information and completing learning tasks, while self-regulation involves the ability to control behavior and emotions to achieve learning goals. Motivation, as a driving force, plays a crucial role in directing learning behavior, both intrinsically and extrinsically. This systematic review method involves the identification, selection, and critical analysis of relevant articles published within a specified time period. Data are comprehensively analyzed to identify patterns and trends that emerge in the relationship between cognitive styles, self-regulation, and motivation in the context of learning. The review findings indicate a significant correlation between cognitive styles and self-regulation with learning motivation. These findings underscore the importance of adapting learning strategies according to individual cognitive styles and developing self-regulation skills to enhance learning motivation. Intrinsic motivation, rooted in internal interests and desires, proves stronger in predicting sustained academic achievement compared to extrinsic motivation dependent on external rewards or punishments. The conclusion of this review emphasizes the need for a holistic educational approach that considers the complex interaction between cognitive styles, self-regulation, and motivation. Practical implications include the development of personalized and differential learning strategies as well as empowering students to manage their own motivation and self-regulation to achieve optimal learning potential.